ANALISIS MINAT BELAJAR SISWA PEREMPUAN TINGKAT ATAS PADA MATA PELAJARAN PENDIDIKAN JASMANI DI SEKOLAH DASAR - Sitinjak, Septian Doly; Sitompul, Deni Ardian; Purba, Ivan Gunawan; Siahaan, Samuel; Nurkadri, Nurkadri (JURNAL KELUARGA SEHAT SEJAHTERA, 2024)
Analysis of upper level female students™ learning interest in physical education in primary scool. Physical education is a subject that requires physical activity. Physical activity becomes a benchmark in determining students™ interest in learning. Learning interest is influenced by internal factros and external factors of upper grade famale students which include 4th, 5th, and 6th, grade famale students, descriptive and inferential analysis will be crried out. This research is a qualitative research instuments in the form of questionnaires and interview results. The results of this study  indicate that 76% of famale students at SD Negeri 068474 medan are categorized as strong. This means that as many as 76% of the total sample have an interest in praticipating in sthe physical education learning process.